DOP75 Surgery and hospitalisations rates in inflammatory bowel disease patients in the Québec provincial database from 199–6 to 2015. (25th January 2019) - Verdon, C; Reinglas, J; Coulombe, J; Gonczi, L; Bessissow, T; Afif, W; Vutcovici, M; Wild, G; Seidman, E; Bitton, A; Brassard, P; Lakatos, P
Abstract: Background: Inflammatory bowel diseases (IBD), including Crohn's disease (CD) and ulcerative colitis (UC), are associated with high healthcare expenditures related to medications, hospitalisations, and surgeries. Our aim was to analyse disease outcomes and treatment algorithms in newly diagnosed IBD patients in Québec over the past 2 decades, comparing periods before and after routine public reimbursement of biologics. Methods: Overall, 34644 newly diagnosed IBD patients (CD: 20644 or 59.5%; M:F CD: 3:4, UC: 1:1; CD <40 years old: 46% vs. UC<40 years old: 35%) were identified from the population-based health insurance database of Québec from 1996 to 2015. The primary and secondary outcomes included time to and probability of first hospitalisation and first major surgery, and medication exposures. Prescription data were collected from the public prescription database (RAMQ). Results: Probability of major surgery increased after 2010 in CD (at 5 years after diagnosis: before and after 2010: 8% (SD: 0.2%) vs.15% (0.6%); p < 0.0001) and UC patients (6% (0.2%) vs. 10% (0.6%); p < 0.0001). Probability of first major surgery Hospitalisations rates remained unchanged, but were higher in CD compared with UC ( p < 0.0001). Probability of first hospitalisation IBD patients on biologicals had overall lower probability of hospitalisations compared with other drug types (overall 5 years probability for all IBD patients using 5-ASA: 37% (0.6%); biologicals: 31% (1.8%), p < 0.0001). Biologicals were more commonly prescribed in CD after 2010 (4% (0.2%) vs. 16% (0.6%), p < 0.0001), especially in patients less than 40 years old at diagnosis. Thiopurine exposure increased in IBD patients after 2010 (CD: 21% (0.4%) vs. 24% (0.6%) p < 0.0001; UC: 13% (0.4%) vs. 16% (0.7%), p < 0.0001), while methotrexate use remained overall low (overall 5 years probability in CD: 4% (0.1%) ;UC: 1% (0.1%); p < 0.0001). Corticosteroid exposure was unchanged before and after 2010 (CD: 31% (0.4%) vs. 30% (0.7%) p = 0.46; UC: 31% (0.5%) vs. 34% (0.9%); p = 0.03). 5-ASA use was higher in UC (40% (0.4%), p < 0.001), while in CD it became lower after 2010 (33% (0.4%) vs. 21% (0.6%), p < 0.0001). Conclusions: The probability of first hospitalisation remained unchanged whilst the probability of first major surgery was increased despite the higher and earlier use of biological therapies in this large population-based inception cohort from Québec. Overall, there was a slight increase in the use of thiopurines and methotrexate, while the use of corticosteroids was unchanged.